Betaine restores epigenetic control and supports neuronal mitochondria in the cuprizone mouse model of multiple sclerosis. Issue 8 (2nd August 2020) - Singhal, Naveen K.; Sternbach, Sarah; Fleming, Sheila; Alkhayer, Kholoud; Shelestak, John; Popescu, Daniela; Weaver, Alyx; Clements, Robert; Wasek, Brandi; Bottiglieri, Teodoro; Freeman, Ernest J.; McDonough, Jennifer
ABSTRACT: Methionine metabolism is dysregulated in multiple sclerosis (MS). The methyl donor betaine is depleted in the MS brain where it is linked to changes in levels of histone H3 trimethylated on lysine 4 (H3K4me3) and mitochondrial impairment. We investigated the effects of replacing this depleted betaine in the cuprizone mouse model of MS. Supplementation with betaine restored epigenetic control and alleviated neurological disability in cuprizone mice. Betaine increased the methylation potential (SAM/SAH ratio), levels of H3K4me3, enhanced neuronal respiration, and prevented axonal damage. We show that the methyl donor betaine and the betaine homocysteine methyltransferase (BHMT) enzyme can act in the nucleus to repair epigenetic control and activate neuroprotective transcriptional programmes. ChIP-seq data suggest that BHMT acts on chromatin to increase the SAM/SAH ratio and histone methyltransferase activity locally to increase H3K4me3 and activate gene expression that supports neuronal energetics. These data suggest that the methyl donor betaine may provide neuroprotection in MS where mitochondrial impairment damages axons and causes disability.